Group lending with heterogeneous types - Gan, Li; Hernandez, Manuel A.; Liu, Yanyan (International Food Policy Research Institute, 2013)
Group lending has been widely adopted in the past thirty years by many microfinance institutions as a means to mitigate information asymmetries when delivering credit to the poor. This paper proposes an empirical method to address the potential omitted-variable problem resulting from unobserved group types when modeling the repayment behavior of group members.